Indicadores de sustentabilidade sob aspectos do lazer e agroturismo em propriedades rurais do município de Marechal Cândido Rondon - PR - Metzner, Cristiano Luiz (2016)
Currently the rural properties are not caracterized mainly as agricultural producers. Other activities have been introduced, along with the traditional activities, with the purpose of aggregating better financial sources to the families and at the same time contributing to the rural development in their realities. This study has the objective of researching the agroturism and leisure in rural properties in Marechal Cândido Rondon PR, and discuss their relationship with the sustainable rural development, identifying the existent projects and analyzing their contributions. The research methodology used was qualitative/descriptive, with a non probabilistic sample to represent the population to be studied, using a form interview as a collecting data instrument, and also descriptive analysis. As a result of this study we have identified five rural properties that perform agroturism and leisure projects and they are: Sítio das Orquídias, Pesque Pague Alli, Pesque Pague Paulista, Cachoeira da Onça and Ricas Trilhas Verdes. All of them more than 10 years operating these projects, most of them also have traditional rural production, but being the agroturism the most profitable income. This income agreggated to the traditional production profit brought better strutuctural and social conditions to the properties, generating more jobs.Another contribution of these projects is the permanence of the children in the property, supporting the activities, and even if going out to study, coming back to help out. The transformations and care with the environment were increased due to the incorporation of the agroturism and leisure projects in the properties, enlarging this idea to the visitors through ambiental education projects, despite lowly in the majority of the farms. In spite of the low governmental financial sources, the private investments are still going on, mantaining the projects in action, and the producers happy to mantain them, and also being these producers presentee in their social relationship with the visitors. At last, we conclude that inside a sustainable rural development perspective, the studied rural properties are developing new work alternatives, beyond the traditional farm ones, with what they are getting benefits and also offering changes to the lifes of the people who work or visit the place, with high gain to the enviroment too